Spanish drivers of the Battery "Ernst Thaelmann" and the German commander of the transport division. Copied from collection Museum für Deutsche Geschichte
Spanish drivers of the Battery "Ernst Thaelmann" and the German commander of the transport division. Copied from collection Museum für Deutsche Geschichte.